1995
DOI: 10.1103/physreve.52.2478
|View full text |Cite
|
Sign up to set email alerts
|

Coupled maps on trees

Abstract: We study coupled maps on a Cayley tree, with local (nearest-neighbor) interactions, and with a variety of boundary conditions. The homogeneous state (where every lattice site has the same value) and the node-synchronized state (where sites of a given generation have the same value) are both shown to occur for particular values of the parameters and coupling constants. We study the stability of these states and their domains of attraction. As the number of sites that become synchronized is much higher compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…In 1995 and 1996, Gade et al 41 and Gade, 42 respectively, showed that synchronization in certain types of networks could have a general form for the analysis of the system's stability. In the 1995 paper, they showed that coupled maps on tree-structured networks would have better synchronization robustness than the same chaotic maps on a regular (e.g., nearest neighbor coupled) lattice.…”
Section: The Beginning Of Chaotic Synchronization In Networkmentioning
confidence: 99%
“…In 1995 and 1996, Gade et al 41 and Gade, 42 respectively, showed that synchronization in certain types of networks could have a general form for the analysis of the system's stability. In the 1995 paper, they showed that coupled maps on tree-structured networks would have better synchronization robustness than the same chaotic maps on a regular (e.g., nearest neighbor coupled) lattice.…”
Section: The Beginning Of Chaotic Synchronization In Networkmentioning
confidence: 99%
“…A periodic attractor of period 3 exists near ε = 0.945, which transforms to intermittent behavior at ε = 0.95, shown in Figure 5. All these dynamics are exhibited by the coupled system (1), since Figure 1 implies that for these parameter values the system is synchronized (provided it has an appropriate connection topology), so the collective behavior is described by (3). Clearly, delays can make the dynamics of the synchronized system quite sensitive to the coupling strength, a feature that is absent in undelayed networks.…”
mentioning
confidence: 99%
“…Usually, such systems have been investigated under the assumption of a certain regularity in the connection topology, where units are coupled to their nearest neighbors or to all other units. Lately, more general networks with random, small-world, scale-free, and hierarchical architectures have been emphasized as appropriate models of interaction [3,4,5,6,7]. On the other hand, realistic modeling of many large networks with non-local interaction inevitably requires connection delays to be taken into account, since they naturally arise as a consequence of finite information transmission and processing speeds among the units.…”
mentioning
confidence: 99%
“…and different types of synchronizations have arisen such as phase synchronization or complete synchronization, etc. Coupled maps [11] have been used to a great extent to understand synchronization in particular [12,13,14,15,16,17,18,19,20,21,27] and complexity in dynamical systems [22,23,24] in general. The paradigm here consists of identical individual maps, typically iterates of a functional equation like the logistic one that produce chaotic dynamics.…”
Section: Introductionmentioning
confidence: 99%